Traumatic dental injuries of the permanent incisors and its relation to malocclusion in patients attending the pedodontic clinic in College of Dentistry, Baghdad University (Mustansiria Dental Journal, 2018)
Dental trauma is a public health problem in young aged patients. The aim of thisstudy was to investigate the percentage and severity of dental trauma andmalocclusion and their correlation, as well as analyze the general risk factors like theeffect of age, gender, causes of the trauma and malocclusion in anterior permanentteeth.The sample of the present study include patients who came to the Pedodonticclinic in the Pedodontic and Preventive department at the College ofDentistry/Baghdad University seeking treatment of traumatized anterior permanentteeth. The traumatized teeth were examined clinically (according to Garcia-Godyclassification) and radiographically. Types of occlusion was determined according toAngle’s classification, while the over jet and overbite were recorded according to thecoding criteria described by Kinnan’s study.In all age groups, the most frequent cause of trauma was found to be falls (61.4%).Enamel and dentin fracture was the most frequently seen type of injury(38.6%) inwhich upper central incisors were the most affected teeth from dentaltrauma(47.7%).Regarding malocclusion, patients with class II malocclusion represent(71.9%) from the total sample, while those with increased over jet (26.3%) in which(66.7) of them seek treatment for two fractured teeth. However, the number of injuredteeth per child was 1.54. Increased overbite was correlated with more sever type ofdental trauma.There is a relationship between malocclusion and fractured anterior teeth in whichmalocclusion will increase the number of fractured teeth as well as the severity ofdental trauma